LACTIC ACIDOSIS IN A PATIENT WITH TYPE 2 DIABETES MELLITUS: A SYSTEMATIC REVIEW - Nur Amelia , Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Lactic acidosis occurs when lactate synthesis exceeds metabolism. Multiple causes of lactic acidosis may coexist in a patient. Attending Rounds exemplifies the theme. This example shows how metformin can complicate type 2 diabetes-related lactic acidosis. Lactic acidosis treatment is controversial, because it must address the cause. Aim: This article examines the link between lactic acidosis in a patient with type 2 diabetes mellitus. Methods: This study showed that it met all of the requirements by looking at the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. So, the experts could make sure that the study was as current as possible. The search method used a number of electronic reference databases, such as Pubmed and SagePub, to look for papers that were published between 2000 and 2023. We didn't look at review papers, articles that had already been published, or articles that were only half done. Result: In the PubMed database, the results of our search brought up 77 articles, whereas the results of our search on SagePub brought up 56 articles. The results of the search conducted for the last year of 2013 yielded a total of 17 articles for PubMed and 6 articles for SagePub. In the end, we compiled a total of 18 papers, 13 of which came from PubMed and five of which came from SagePub. We included five research that met the criteria. Conclusion: Studies consistently show that blood lactate levels in patients taking metformin are increased, but are not significantly associated with the risk of developing lactic acidosis.